Association Analysis of Indel Variant of IGFBP2 Gene with Slaughter Performances of Jiaji Muscovy Ducks - J Hu; X Ji; Y Qi; X Zhang; T Xu; L Gu (Brazilian Journal of Poultry Science, 2025)
ABSTRACT The IGFBP2 gene plays an important role in regulating animal energy metabolism. It is one of the key candidate genes for poultry growth and meat-related traits. Therefore, the present study screened the indel loci of the IGFBP2 gene to investigate the effects of these indels on the growth and slaughter performance of Jiaji Muscovy ducks. Using our previous genome resequencing data, a 14 bp indel was found on the first intron of the IGFBP2 gene. Specific primers were designed and synthesized, and genotyping was carried out in 102 Jiaji Muscovy ducks using PCR and agarose gel electrophoresis. Association analyses between growth and slaughter traits, and genotyping results were conducted for the Jiaji Muscovy ducks. Meanwhile, the expressions of IGFBP2 mRNA in the breast muscle of individuals with different genotypes were detected using RT-qPCR. The results showed that the pre-slaughter body weight, carcass weight, half-clean rump weight, full-clean rump weight, leg muscle weight, pectoral muscle weight, abdominal fat, and skin fat content of Jiaji Muscovy ducks with indel mutation were significantly reduced, and the expression level of IGFBP2 mRNA was increased in the breast muscle of the mutant individuals. This indel locus can regulate the expression level of the IGFBP2 gene in muscles, thus affecting the growth and slaughter performance of Jiaji Muscovy ducks.